Devising a method for assessing the residual resource and efficiency of tool utilization based on the analysis of dimensional wear - Krupa, Volodymyr; Kobelnyk, Volodymyr; Viuk, Denys; Zakharii, Andrii; Bei, Mychailo (Eastern-European Journal of Enterprise Technologies, 2026)
This study considers a tool rejection system in mechanical engineering production with a single or small-batch type. The task addressed is to substantiate assessment of the degree of wear of replaceable carbide inserts that are rejected during single and small-scale production based on the results of current diagnostics. The proposed approach could make it possible to track possible failures or premature rejection and unjustified losses based on a qualitative analysis of actual wear using probabilistic-stochastic methods. A method for assessing the condition of rejected carbide inserts has been proposed, underlying which is measuring their wear on the back surface, transition to dimensional wear, their statistical processing and grouping by wear level. Experimental studies were conducted on carbide inserts used in a milling cutter during roughing of steels under conditions of cyclic shock loads. It was found that the magnitude of dimensional wear obeys the normal distribution law with the following characteristics: mean value mm, dispersion of scattering D(h) = 0.00135 mm2, and mean square deviation σ(h) = 0.0375 mm. Dependences were derived and the percentage composition of rejected inserts was determined: 50.91% of inserts can still be used (with different resources); 1.17% of inserts are excessively worn (which could lead to defects); and 47.91% of inserts are correctly rejected during production. The proposed methodology could be practically applied without complex measuring equipment and specialized monitoring systems, which makes it suitable for implementation during single and small-scale production. Implementing the method makes it possible to reduce unjustified rejected tools, increase the efficiency of the diagnostic system, and ensure the economy of material resources of an enterprise.